Australian libraries and the promotion of LGBTQI+ rights. Issue 1 (2nd January 2019) - Carter, Josh
ABSTRACT: This research summary sets out to analyse the role that Australian libraries play in the promotion of LGBTQI+ rights. It will provide a clearer understanding of the measures taken by Australian libraries to promote equality, advocate for social change and stop the marginalisation of its LGBTQI+ users.